Internet Question and Answer (iQ&A) a Web-based survey technology. - Dennis, R.A (IEEE Transactions on information technology in biomedicine)
Presents "InternetQuestion and Answer" (iQ&A), a Web-based survey development and implementation technology, which has been designed for constructing online surveys for educational, medical or administrative purposes. The iQ&A system is a three-tiered database-backed Web system that has been developed to support a wide range of applications. Surveys are considered as general data collection instruments and include a wide field of application. iQ&A facilitates rapid survey construction and administration, which is ideally suited for biomedical research as well as other research and educational activities. Full report management capabilities provide the survey publisher with online access to current information on survey responses. Current implementations of this technology in the areas of biomedical applications of clinical trials, longitudinal research and other research-related systems are presented. Further refinement of the current system should lead to a powerful general survey technology for broad-based applications.